2017
DOI: 10.1002/jso.24704
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a nomogram to estimate the pretest probability of cancer in Chinese patients with solid solitary pulmonary nodules: A multi‐institutional study

Abstract: We developed and validated a nomogram that can estimate the pretest probability of malignant solid SPNs, which can assist clinical physicians to select and interpret the results of subsequent diagnostic tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
126
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(141 citation statements)
references
References 27 publications
(84 reference statements)
3
126
2
Order By: Relevance
“…Studies have shown that the performance of models is influenced by the composition of the study population. The Mayo 30,31 and Herder 31 models were successfully validated in an independent population in which the prevalence of malignant nodules was similar to that in the original…”
Section: F-fdg Pet/ct-based Clinical Prediction Modelmentioning
confidence: 99%
“…Studies have shown that the performance of models is influenced by the composition of the study population. The Mayo 30,31 and Herder 31 models were successfully validated in an independent population in which the prevalence of malignant nodules was similar to that in the original…”
Section: F-fdg Pet/ct-based Clinical Prediction Modelmentioning
confidence: 99%
“…Growing use of chest computed tomography (CT) has resulted in the identification of over millions of solitary pulmonary nodules (SPNs) each year [1]. Although only approximately 30% of such SPNs are malignant, decisions to undergo surgical resection or pursue CT surveillance hinge on the probability of malignancy for the identified SPNs [2]. Tissue biopsy, radiographic imaging modalities, and serum biomarkers can help determine the malignancy.…”
Section: Introductionmentioning
confidence: 99%
“…30 Besides, another three models were also established for solid nodules based on a Chinese population (AUC=0.85~0.87). [31][32][33] Compared to these four models, the current solid-nodule models shared some similar risk factors, such as age, sex, history of malignancy, morphology, and serum CEA, but some novel markers like V25, RV/TLC, serum lymphocyte, CYFRA21-1, and NSE were also identified. As for model performance, these four were a little better than our models (AUC=0.82), which can be associated with some valuable predictors they enrolled, such as enhancement, VDT, as well as maximum uptake value of nodules.…”
Section: Discussionmentioning
confidence: 96%
“…Besides, one study also enrolled calcification in the model. 33 Anyway, all these solid-nodule models demonstrated good performance, and clinicians can choose the most appropriate one according to the variable availability and nodule similarity where models were derived.…”
Section: Discussionmentioning
confidence: 99%